2023
DOI: 10.1039/d3ob00060e
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and scalable synthesis of a persistent abscisic acid analog (+)-tetralone ABA

Abstract: An efficient and scalable synthesis of persistent abscisic acid analog (+)-tetralone ABA. (+)-Me ABA was converted to (+)-tetralone Me ABA through a one-pot regioselective Knoevenagel condensation, cyclization, and oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Tetralone ABA, a lead compound of (+)- 5 and (+)- 6 , shows higher agonist activity than ABA in Arabidopsis seed germination, 26 probably because of the long life expectancy of the hydroxylated product, 8′-hydroxy-tetralone ABA, which has ABA-like activity in plants. 2,21 Although 8′-hydroxy-ABA possesses biological activity, 27 this compound spontaneously isomerizes to the lower active metabolite PA. Based on these observations, we initially hypothesize that (+)- 5 showed stronger bioactivity compared to (+)-BP2A because of the persistence of its hydroxylated product, 8′-hydroxy-tetralone-BP2A. However, we found that the bioactivities of (+)- 5′ and (+)- 6′ (carboxylate forms) were less than those of corresponding methyl esters (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tetralone ABA, a lead compound of (+)- 5 and (+)- 6 , shows higher agonist activity than ABA in Arabidopsis seed germination, 26 probably because of the long life expectancy of the hydroxylated product, 8′-hydroxy-tetralone ABA, which has ABA-like activity in plants. 2,21 Although 8′-hydroxy-ABA possesses biological activity, 27 this compound spontaneously isomerizes to the lower active metabolite PA. Based on these observations, we initially hypothesize that (+)- 5 showed stronger bioactivity compared to (+)-BP2A because of the persistence of its hydroxylated product, 8′-hydroxy-tetralone-BP2A. However, we found that the bioactivities of (+)- 5′ and (+)- 6′ (carboxylate forms) were less than those of corresponding methyl esters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exogenously applied ABA and its analogs are inactivated by hydroxylation of the C8′ methyl group and also by glycosylation of the C1 carboxy group. 2,28 The methyl ester group of (+)- 5 may prevent rapid glycosylation of the C1 position and contribute to its persistence in plants, although we cannot exclude the possibility that other pharmacokinetic parameters may contribute to the superior activity of (+)- 5 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific receptors for abscisic acid (ABA), a plant hormone (Figure ), have emerged as promising targets for these antitranspirants. When there is a water shortage, the endogenous ABA levels increase rapidly, activating the ABA signaling pathway, which leads to stomatal closure and reduced water loss through transpiration. , Additionally, this activation induces the expression of various stress-responsive genes involved in processes such as osmotic regulation, dehydration tolerance, and the management of reactive oxygen species. Researches indicate that applying exogenous ABA significantly improves crop productivity during drought conditions. , However, the practical use of natural ABA in agriculture is limited due to several main drawbacks associated with its use as a plant growth regulator. These drawbacks include the complex structure of natural ABA, which leads to high production costs and challenges for large-scale industrial production, susceptibility to isomerization and deactivation under light conditions, and sensitivity to metabolic deactivation within the plant’s physiological system . Therefore, there is urgent interest in developing new small molecules with a favorable structure and agonistic activity toward ABA receptors.…”
Section: Introductionmentioning
confidence: 99%